Accelerated corrosion experiment system and method for circuit board
By forming a composite electromagnetic field at the circuit board sample and adjusting the electric field and magnetic induction strength, the problem of long experimental cycle of indoor accelerated corrosion of circuit boards in the prior art is solved, and efficient corrosion of circuit board corrosion samples is achieved, and experimental operations are simplified.
Patent Information
- Application Number
- CN202411439012.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to effectively shorten the cycle of accelerated corrosion experiments in circuit boards. There are limitations on existing methods such as increasing temperature and increasing electrolyte concentration, which cannot significantly increase the corrosion rate.
The corrosion process of the circuit board is accelerated by forming a composite electromagnetic field, including a combination of electric field and magnetic field, at the circuit board sample, and adjusting the electric field and magnetic induction intensity. The electric field unit consists of an electric field generator and a metal mesh, and the magnetic field unit consists of an electromagnet and an AC power supply. The corrosion rate is controlled by adjusting the electric field and magnetic induction intensity.
It significantly improves the corrosion rate of the circuit board corrosion samples, simplifies the device structure and operation methods, and is suitable for studying indoor accelerated corrosion experiments of circuit boards.
Smart Images

Figure CN119198521A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal corrosion, and in particular to an accelerated corrosion experiment system and method for a circuit board. Background Art
[0002] The corrosion of metals in electrolyte solutions is a complex redox process. The field corrosion test cycle is long, usually several months, and some corrosion-resistant metals even have a long corrosion cycle of more than 1 year. Indoor accelerated corrosion testing is an important method for evaluating the corrosion performance of metals. It can significantly shorten the corrosion test cycle. Shortening the indoor corrosion test cycle can improve the test efficiency and reduce the test cost.
[0003] In the prior art, there is no technical inspiration for improving the efficiency of indoor accelerated corrosion experiments for circuit boards in the disclosed Chinese patent documents. There are two main methods for controlling indoor accelerated corrosion experiments disclosed. One is to increase the corrosion rate by increasing the experimental temperature, and the other is to increase the corrosion rate by increasing the electrolyte concentration in the solution. Increasing the corrosion rate by increasing the experimental temperature is a relatively common method. Since the heating temperature of the electrolyte solution cannot be too high and cannot exceed the boiling point of the electrolyte solution, the effect on improving the corrosion rate is limited. Increasing the concentration of the electrolyte in the solution to shorten the corrosion cycle is effective, but the control of the electrolyte concentration is usually determined by the working environment. For example, in an indoor accelerated corrosion experiment simulating seawater, the electrolyte concentration is 3.5% and cannot be changed at will. The above situation is not conducive to relevant experimental research on indoor accelerated corrosion of indoor circuit boards. Therefore, it is necessary to provide a device for improving the efficiency of accelerated corrosion experiments for circuit boards. Summary of the invention
[0004] The object of the present invention is to provide a system and method for accelerating corrosion experiment of circuit boards.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] An accelerated corrosion test system for a circuit board, comprising:
[0007] Electric field unit,
[0008] including an electric field generator;
[0009] The electric field generator adjusts the output voltage to control the electric field intensity generated by the electric field unit;
[0010] The positive and negative electrodes of the electric field generator are respectively connected to the metal mesh; the metal mesh is fixed by a plurality of rubber columns;
[0011] The electric field unit can adjust the electric field strength at the circuit board sample;
[0012] A magnetic field unit, the magnetic field unit includes an AC power supply, and the AC power supply is connected to the electromagnet;
[0013] The magnetic induction intensity at the circuit board sample is controlled by adjusting the distance between the magnetic field unit and the circuit board sample;
[0014] A sample corrosion unit comprises a glass container filled with an electrolyte solution, wherein a circuit board corrosion sample is placed in the electrolyte solution of the glass container;
[0015] The electric field unit and the magnetic field unit form a required composite field of electric field and magnetic field at the circuit board sample, which can accelerate the corrosion process of the circuit board sample.
[0016] Furthermore, the rubber column is an insulator. The lower end of the rubber column is fixed on the base.
[0017] Furthermore, the metal mesh is a wire mesh, and the front and rear ends of the metal mesh are respectively connected to two rubber columns.
[0018] Furthermore, the electric field generator is a BM type electric field generator, and the positive and negative electrodes are respectively connected to two metal meshes through wires and are conductive.
[0019] Furthermore, the electromagnet is connected to an AC power source through a wire and is turned on.
[0020] An accelerated corrosion test method for a circuit board, the method comprising:
[0021] Setting up a sample corrosion unit, and placing the circuit board corrosion sample into a glass container of an electrolyte solution;
[0022] An electric field generator is provided, and the electric field intensity generated by the electric field unit is controlled by adjusting the output voltage of the electric field generator;
[0023] An electric field generator is set, and the angle between the electric field direction generated by the electric field unit and the corrosion surface of the sample is controlled to be no greater than 15° through the relative position of the metal mesh and the relative position of the metal mesh and the corrosion unit;
[0024] The electric field unit adjusts the electric field strength at the circuit board sample, and the input voltage range of the electric field unit is greater than 1KV;
[0025] A magnetic field unit is set, and the magnetic induction intensity at the circuit board sample is controlled by adjusting the distance between the magnetic field unit and the circuit board sample; the input voltage of the magnetic field unit is 24V;
[0026] By adjusting the relative position of the magnetic field unit and the corrosion unit, the magnetic field lines generated by the magnetic field unit are controlled to be parallel to the corrosion surface of the sample;
[0027] The electric field unit and the magnetic field unit form the required composite field of electric field and magnetic field at the circuit board sample. The composite electromagnetic field includes a combination of static magnetic field and alternating electric field, and also includes a combination of dynamic magnetic field and alternating electric field. The corrosion process of the circuit board sample is accelerated; by controlling the input voltage of the electric field unit, the electrostatic field of different strengths is generated on the surface of the circuit board corrosion sample; by adjusting the distance between the magnetic field unit and the corrosion sample, the magnetic induction intensity on the surface of the circuit board corrosion sample is greater than 0.15T.
[0028] Furthermore, the electrolyte solution is a sodium chloride solution with a mass fraction of 3.5%.
[0029] Furthermore, when the corrosion process proceeds in the corrosion system, the corrosion cells contain corrosive ions.
[0030] Furthermore, when the corrosion process proceeds in the corrosion system, the corrosive ions include chloride ions and hydroxide ions.
[0031] Furthermore, the circuit board corrosion specimen is a circuit board cold mounting specimen.
[0032] Furthermore, the circuit board corrosion sample includes at least one of the following: red copper, copper-nickel alloy, copper-tin alloy, and copper-beryllium alloy.
[0033] The significant advantages of the present invention are: 1. The electric field strength generated by the electric field unit is controlled by adjusting the output voltage of the electric field generator, thereby controlling the electric field strength at the circuit board sample; the magnetic induction strength generated by the magnetic field unit is controlled by setting the output voltage of the AC power supply, thereby adjusting the magnetic induction strength at the circuit board sample; 2. The required composite field of the electric field and the magnetic field is formed at the circuit board sample; the composite field of the electric field and the magnetic field will accelerate the corrosion process of the circuit board sample; it is suitable for studying corrosion experiments related to the accelerated corrosion rate in the circuit board sample room; 3. At the same time, the device structure of the present invention is simple, and the operation method provided is simple and convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a structural schematic diagram of the accelerated corrosion test system of the present invention.
[0035] Figure 2 This is a graph showing the influence of electric field strength and magnetic induction strength on corrosion resistance of circuit board samples in a 3.5% mass fraction sodium chloride solution.
[0036] Figure 3 This is a graph showing the influence of the electric field strength and magnetic induction intensity on the corrosion polarization curve of a circuit board sample in a sodium chloride solution with a mass fraction of 3.5%.
[0037] Figure 4This is a graph showing the influence of electric field strength and magnetic induction strength on corrosion resistance of circuit board samples in a 3.5% mass fraction sodium chloride solution.
[0038] Figure 5 This is a graph showing the influence of electric field strength and magnetic induction strength on corrosion resistance of circuit board samples in a 3.5% mass fraction sodium chloride solution.
[0039] Figure 6 This is a graph showing the influence of the electric field strength and magnetic induction intensity on the corrosion polarization curve of a circuit board sample in a sodium chloride solution with a mass fraction of 3.5%.
[0040] In the figure, 1. rubber column, 2. metal mesh, 3. base, 4. wire, 5. BM type electric field generator, 6. wire, 7. electromagnet, 8. wire, 9. AC power supply, 10. pad, 11. electrolyte solution, 12. glass container, 13. workbench, 14. circuit board corrosion sample. DETAILED DESCRIPTION
[0041] In order to more clearly understand the technical essence and beneficial effects of the present invention, the applicant will explain the specific implementation methods of the present invention in detail below in conjunction with the accompanying drawings. However, the description of the embodiments is not a limitation of the present invention. Any equivalent changes made based on the concept of the present invention that are merely formal but not substantial should be regarded as within the scope of the technical solution of the present invention and be protected.
[0042] An accelerated corrosion experiment system for a circuit board comprises an electric field unit; a magnetic field unit; and a sample corrosion unit;
[0043] The electric field unit includes four rubber columns 1, two metal meshes 2, and a BM type electric field generator 5;
[0044] The rubber column 1 is an insulator. The lower end of the rubber column 1 is fixed on the base 3. The metal mesh 2 is a wire mesh. The front and rear ends of the metal mesh 2 are respectively connected to the two rubber columns 1. The positive and negative electrodes of the BM type electric field generator 5 are respectively connected to the two metal meshes 2 through the wire 4 and the wire 6 and are conductive.
[0045] The magnetic field unit includes an electromagnet 7 and an AC power source 9. The electromagnet 7 is connected to the AC power source 9 through a wire 8 and is turned on. The magnetic field unit is placed on a washer 10.
[0046] The sample corrosion unit includes a glass container 12 filled with an electrolyte solution 11, and a circuit board corrosion sample 14 is placed in the electrolyte solution 11. The sample corrosion unit is set on a workbench 13.
[0047] The entire unit is placed on a base.
[0048] The accelerated corrosion test method is carried out by the above device, and the circuit board corrosion sample 14 is placed in a glass container of the electrolyte solution 11;
[0049] The BM type electric field generator 5 adjusts the output voltage to control the electric field intensity generated by the electric field unit;
[0050] The electric field unit adjusts the electric field strength at the circuit board sample 14, and the input voltage range of the electric field unit is greater than 1KV;
[0051] The magnetic induction intensity at the circuit board sample 14 is controlled by adjusting the distance between the magnetic field unit 9 and the circuit board sample; the input voltage of the magnetic field unit is 24V;
[0052] The electric field unit and the magnetic field unit form a composite field of electric field and magnetic field required at the circuit board sample 14. The composite electromagnetic field includes a combination of static magnetic field and alternating electric field, and also includes a combination of dynamic magnetic field and alternating electric field. The corrosion process of the circuit board sample is accelerated; by controlling the input voltage of the electric field unit, the surface of the circuit board corrosion sample generates electrostatic fields of different intensities; by adjusting the distance between the magnetic field unit and the corrosion sample 14, the magnetic induction intensity at the surface of the circuit board corrosion sample 14 is greater than 0.15T.
[0053] The circuit board corrosion sample in the present invention is a circuit board cold mounting sample. In addition, the circuit board corrosion sample is at least one of the following: red copper, copper-nickel alloy, copper-tin alloy, copper-beryllium alloy.
[0054] The following specific experiments were carried out by the device of the present invention:
[0055] Embodiment 1:
[0056] Effect of electric field strength and magnetic induction intensity on corrosion resistance of circuit board samples in 3.5% sodium chloride solution:
[0057] The circuit board was cut into a group of samples with a size of 10mm×2mm×4mm by wire cutting, and then the samples were embedded in epoxy resin as working electrodes. Before the test, the electrode surface was polished to 2000 grains with sandpaper, then polished to mirror finish with diamond paste, then ultrasonically cleaned with ethanol and dried with cold air. The electrode was then immersed and corroded. The corrosive liquid was a sodium chloride solution with a mass fraction of 3.5%, and the corrosion time was 0 day, 1 day, 2 days, 3 days, and 4 days. The input voltage of the magnetic field unit was 24V, and the magnetic lines were parallel to the corrosion surface of the sample. The input voltage of the electric field unit was 0KV, 2KV, and 3KV, respectively, and the angle between the direction of the electric field strength and the corrosion surface of the sample was 10°. Then a three-electrode test was used to show the variation of the Warburg resistance of the circuit board sample with the electric field strength and magnetic induction intensity. The results are shown in the figure below. Figure 2As shown in the figure, the electric field strength and magnetic induction strength have a significant effect on the Warburg resistance of the circuit board sample. At different corrosion times, when the input voltage of the electric field unit is greater than 1KV, the Warburg resistance is significantly reduced, that is, the corrosion rate is increased. The results show the effectiveness of the device in improving the electrolytic corrosion efficiency of circuit board samples.
[0058] Embodiment 2:
[0059] The influence of electric field strength and magnetic induction intensity on the polarization curve of the circuit board sample in a sodium chloride solution with a mass fraction of 3.5% on the corrosion process:
[0060] The circuit board was cut into a group of samples with a size of 10mm×2mm×4mm by wire cutting, and then the samples were embedded in epoxy resin as working electrodes. Before the test, the electrode surface was grinded to 2000 grains with sandpaper, then polished to mirror finish with diamond paste, then ultrasonically cleaned with ethanol and dried with cold air. The electrode was then immersed and corroded. The corrosive liquid was a sodium chloride solution with a mass fraction of 3.5%, and the corrosion time was 6 hours. The input voltage of the magnetic field unit was 24V, the magnetic lines were parallel to the corrosion surface of the sample, the input voltages of the electric field unit were 0KV, 0.5KV, 1KV, and 2KV, respectively, and the angle between the direction of the electric field intensity and the corrosion surface of the sample was 15°. Then a three-electrode test was used to determine the variation of the polarization curve of the circuit board sample with the electric field intensity and the magnetic induction intensity. The results are shown in the figure. Figure 3 As shown in the figure, the electric field strength and magnetic induction strength have a significant effect on the polarization curve of the circuit board sample. When the input voltage of the magnetic field unit is 24V and the input voltage of the electric field unit is greater than 1KV, the corrosion potential of the circuit board sample is significantly reduced, that is, the corrosion resistance of the circuit board sample is significantly reduced. The results show the effectiveness of the device in accelerating the electrolytic corrosion experiment of the circuit board sample.
[0061] Embodiment 3:
[0062] Effect of electric field strength and magnetic induction intensity on corrosion resistance of circuit board samples in 3.5% sodium chloride solution:
[0063] The circuit board was cut into a group of samples with a size of 10mm×2mm×4mm by wire cutting, and then the samples were embedded in epoxy resin as working electrodes. Before the test, the electrode surface was sanded to 2000 grains with sandpaper, then polished to mirror finish with diamond paste, then ultrasonically cleaned with ethanol and dried with cold air. The electrode was then immersed and corroded. The corrosive liquid was a sodium chloride solution with a mass fraction of 3.5%, and the corrosion time was 1 day. The input voltage of the magnetic field unit was 24V, and the magnetic lines were parallel to the corrosion surface of the sample. By adjusting the distance between the magnetic field unit and the sample, the magnetic induction intensity on the sample surface was 0T, 0.1T, 0.15T, and 0.2T. The input voltage of the electric field unit was 5KV, and the angle between the direction of the electric field intensity and the corrosion surface of the sample was 10°. Then a three-electrode test was used to test the variation of the Nyquist impedance of the circuit board sample with the electric field intensity and magnetic induction intensity. The results are shown in the figure. Figure 4 As shown in the figure, the electric field strength and magnetic induction strength have a significant effect on the Nyquist impedance of the circuit board sample. When the magnetic induction strength is greater than 0.15 T, the Nyquist impedance is significantly reduced, that is, the corrosion rate is increased. The results show the effectiveness of the device in improving the electrolytic corrosion efficiency of circuit board samples.
[0064] Embodiment 4:
[0065] Effect of electric field strength and magnetic induction intensity on corrosion resistance of circuit board samples in 3.5% sodium chloride solution:
[0066] The circuit board was cut into a group of samples with a size of 10mm×2mm×4mm by wire cutting, and then the samples were embedded in epoxy resin as working electrodes. Before the test, the electrode surface was sanded to 2000 grains with sandpaper, then polished to mirror finish with diamond paste, then ultrasonically cleaned with ethanol and dried with cold air. The electrode was then immersed and corroded. The corrosive liquid was a sodium chloride solution with a mass fraction of 3.5%, and the corrosion time was 1 day. The input voltage of the magnetic field unit was 24V, and the magnetic lines were parallel to the corrosion surface of the sample. By adjusting the distance between the magnetic field unit and the sample, the magnetic induction intensity on the sample surface was 0.2T. The input voltage of the electric field unit was 5KV, and the angles between the direction of the electric field intensity and the corrosion surface of the sample were 0°, 10°, 15°, and 20°. Then a three-electrode test was used to test the variation of the Nyquist impedance of the circuit board sample with the electric field intensity and magnetic induction intensity. The results are shown in the figure. Figure 5 As shown in the figure, the electric field strength and magnetic induction strength have a significant effect on the Nyquist impedance of the circuit board sample. When the angle between the electric field strength direction and the sample corrosion surface is not greater than 15°, the Nyquist impedance is significantly reduced, that is, the corrosion rate is increased. The results show the effectiveness of the device in improving the electrolytic corrosion efficiency of circuit board samples.
[0067] Embodiment 5:
[0068] Effect of electric field strength and magnetic induction intensity on corrosion resistance of circuit board samples in 3.5% sodium chloride solution:
[0069] The circuit board was cut into a group of samples with a size of 10mm×2mm×4mm by wire cutting, and then the samples were embedded in epoxy resin as working electrodes. Before the test, the electrode surface was sanded to 2000 grains with sandpaper, then polished to mirror finish with diamond paste, then ultrasonically cleaned with ethanol and dried with cold air. The electrode was then immersed and corroded. The corrosive liquid was a sodium chloride solution with a mass fraction of 3.5%, and the corrosion time was 1 day. The input voltage of the magnetic field unit was 24V, and the angles between the magnetic lines and the corrosion surface of the sample were 0°, 5°, 10°, and 15°. By adjusting the distance between the magnetic field unit and the sample, the magnetic induction intensity on the sample surface was 0.2T. The input voltage of the electric field unit was 5KV, and the direction of the electric field intensity was parallel to the corrosion surface of the sample. Then a three-electrode test was used to determine the variation of the polarization curve of the circuit board sample with the electric field intensity and magnetic induction intensity. The results are shown in the figure. Figure 6 As shown in the figure, the electric field strength and magnetic induction strength have a significant effect on the polarization curve of the circuit board sample. When the magnetic field lines are parallel to the corrosion surface of the sample, that is, when the angle between the magnetic field lines and the corrosion surface of the sample is 0°, the corrosion potential of the circuit board sample is the lowest, that is, the corrosion rate of the circuit board sample is the highest. The results show the effectiveness of the device in accelerating the electrolytic corrosion experiment of circuit board samples.
Claims
1. An accelerated corrosion test system for circuit boards, characterized in that: include Electric field unit, including an electric field generator; The electric field generator adjusts the output voltage to control the electric field intensity generated by the electric field unit; The positive and negative electrodes of the electric field generator are respectively connected to the metal mesh; the metal mesh is fixed by a plurality of rubber columns; The electric field unit can adjust the electric field strength at the circuit board sample; Magnetic field unit, The magnetic field unit includes an AC power source connected to an electromagnet; The magnetic field unit can control the magnetic induction intensity at the circuit board sample by the output voltage of the AC power supply; Specimen corrosion unit, It includes a glass container filled with an electrolyte solution, in which a circuit board corrosion sample is placed; The electric field unit and the magnetic field unit form a required composite field of electric field and magnetic field at the circuit board sample, which can accelerate the corrosion process of the circuit board sample.
2. The accelerated corrosion test system for circuit boards according to claim 1, characterized in that: The rubber column is an insulator.
3. The accelerated corrosion test system for circuit boards according to claim 1 or 2, characterized in that: The lower end of the rubber column is fixed on the base.
4. The accelerated corrosion test system for circuit boards according to claim 1, characterized in that: The metal mesh is a wire mesh.
5. The accelerated corrosion test system for circuit boards according to claim 4, characterized in that: The front and rear ends of the metal net are respectively connected to two rubber columns.
6. The accelerated corrosion test system for circuit boards according to claim 1, characterized in that: The electric field generator is a BM type electric field generator, and the positive and negative electrodes are respectively connected to two metal meshes through wires and are conductive.
7. The accelerated corrosion test system for circuit boards according to claim 1, characterized in that: The electromagnet is connected to an AC power source through a wire and is turned on.
8. An accelerated corrosion test method for a circuit board, characterized in that: The method includes: Setting up a sample corrosion unit, and placing the circuit board corrosion sample into a glass container of an electrolyte solution; An electric field generator is provided, and the electric field intensity generated by the electric field unit is controlled by adjusting the output voltage of the electric field generator; An electric field generator is set, and the angle between the electric field direction generated by the electric field unit and the corrosion surface of the sample is controlled to be 15° or less by adjusting the relative position of the metal mesh and the relative position of the metal mesh and the corrosion unit; The electric field unit adjusts the electric field strength at the circuit board sample, and the input voltage of the electric field unit is greater than 1KV; A magnetic field unit is set, and the magnetic induction intensity at the circuit board sample is controlled by adjusting the distance between the magnetic field unit and the circuit board sample; the input voltage of the magnetic field unit is 24V; By adjusting the relative position of the magnetic field unit and the corrosion unit, the magnetic field lines generated by the magnetic field unit are controlled to be parallel to the corrosion surface of the sample; The electric field unit and the magnetic field unit form the required composite field of electric field and magnetic field at the circuit board sample; the corrosion process of the circuit board corrosion sample is accelerated; the electrostatic field of different intensities is generated at the surface of the circuit board corrosion sample by controlling the input voltage of the electric field unit; the magnetic induction intensity at the surface of the circuit board corrosion sample is greater than 0.15T by adjusting the distance between the magnetic field unit and the corrosion sample.
9. The accelerated corrosion test method for circuit boards according to claim 8, characterized in that: The electrolyte solution is a sodium chloride solution with a mass fraction of 3.5%.
10. The accelerated corrosion test method for circuit boards according to claim 8, characterized in that: When the corrosion process is carried out in the corrosion system, the corrosion unit contains corrosive ions, and the corrosive ions include: chloride ions and hydroxide ions; the circuit board corrosion sample is a circuit board cold mounting sample; the circuit board corrosion sample includes one of the following: red copper, copper-nickel alloy, copper-tin alloy or copper-beryllium alloy.
